Effect of Hydrothermal Treatment and Milling Parameters on Milling and Nutritional Qualities of Finger Millet (Eleusine coracana) - Kushwaha, Anurag; Singh, Anupama; Sirohi, Ranjna; Tarafdar, Ayon (Journal of Agricultural Engineering, 2019)
The conditions for degree of pearling of finger millets were optimised based on its quality attributes. Empirical models were developed to predict quality parameters for different sets of milling conditions of dispersed density (430 kg.m-3, 495 kg.m-3, 560 kg.m-3), residence time (10 min, 12 min, 14 min) and roller speed (1000 rpm, 1200 rpm, 1400 rpm) for both untreated and hydrothermally treated finger millet. It was found that hydrothermal treatment could improve pearling efficiency and reduce anti-nutrients while retaining nutritional components to some extent. A model correlating the effect of degree of pearling with pearling efficiency, protein, tannin and calcium content of hydrothermally treated finger millets was also developed with a satisfactory level of accuracy (R2 = 0.997). This equation served to determine the required degree of pearling for any given set of milling conditions. At optimized quality parameters, the degree of pearling for finger millet was 7.4 per cent.